A comparative view of early development in the corals Favia lizardensis, Ctenactis echinata, and Acropora millepora - morphology, transcriptome, and developmental gene expression. Issue 1 (December 2016) - Okubo, Nami; Hayward, David; Forêt, Sylvain; Ball, Eldon
Abstract Background Research into various aspects of coral biology has greatly increased in recent years due to anthropogenic threats to coral health including pollution, ocean warming and acidification. However, knowledge of coral early development has lagged. The present paper describes the embryonic development of two previously uncharacterized robust corals, Favia lizardensis (a massive brain coral) andCtenactis echinata (a solitary coral) and compares it to that of the previously characterized complex coral, Acropora millepora, both morphologically and in terms of the expression of a set of key developmental genes. Results Illumina sequencing of mixed age embryos was carried out, resulting in embryonic transcriptomes consisting of 40605 contigs forC.echinata (N50 = 1080 bp) and 48536 contigs forF.lizardensis (N50 = 1496 bp). The transcriptomes have been annotated against Swiss-Prot and were sufficiently complete to enable the identification of orthologs of many key genes controlling development in bilaterians. Developmental series of images of whole mounts and sections reveal that the early stages of both species contain a blastocoel, consistent with their membership of the robust clade. In situ hybridization was used to examine the expression of the developmentally important genesbrachyury, chordin andforkhead . The expression ofbrachyury andforkhead was consistent with that previously reported forAcropora and allowed us to confirm that the pseudo-blastopore sometimes seen in robust corals such asFavia spp. is not directly associated with gastrulation.C.echinata chordin expression, however, differed from that seen in the other two corals. Conclusions Embryonic transcriptomes were assembled for the brain coralFavia lizardensis and the solitary coralCtenactis echinata . Both species have a blastocoel in their early developmental stages, consistent with their phylogenetic position as members of the robust clade. Expression of the key developmental genesbrachyury, chordin andforkhead was investigated, allowing comparison to that of their orthologs inAcropora, Nematostella and bilaterians and demonstrating that even within the Anthozoa there are significant differences in expression patterns.